2001
DOI: 10.1053/gast.2001.23257
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory role of phosphatidylinositol 3-kinase on TNF-α–Induced cyclooxygenase 2 expression in colonic epithelial cells

Abstract: COX-2 is negatively regulated by PI 3-kinase; we propose that the inhibitory effect of IL-4 and IL-13 is mediated via a PI 3-kinase-dependent pathway. This mechanism does not appear to involve NF-kappaB because PI 3-kinase inhibition did not alter NF-kappaB binding activity. TNF-alpha can activate PI 3-kinase directly in addition to inducing COX-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
1
8

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 64 publications
4
42
1
8
Order By: Relevance
“…HGF is a well-known activator of PI3K/ Akt in various cells, including REPON (Supplemental Fig. 2C), and activation of PI3K/Akt by IL-1b and TNF-a is observed in some cell types [22,23]. We speculated that the PI3K/Akt pathway might be involved in the suppression of the nephrin gene in podocytes.…”
Section: Molecular Mechanisms Involved In Transcriptionalmentioning
confidence: 96%
“…HGF is a well-known activator of PI3K/ Akt in various cells, including REPON (Supplemental Fig. 2C), and activation of PI3K/Akt by IL-1b and TNF-a is observed in some cell types [22,23]. We speculated that the PI3K/Akt pathway might be involved in the suppression of the nephrin gene in podocytes.…”
Section: Molecular Mechanisms Involved In Transcriptionalmentioning
confidence: 96%
“…1). Three samples (16,19,20) showed minor effects. None of the 19 tested lipid fractions of fecal water had an effect on the PGE 2 production (Fig.…”
Section: Fractionation Of Fecal Waters With Cox-2 Inhibitory Activitymentioning
confidence: 97%
“…This enzyme is not normally expressed in the colon, but it can be induced by growth factors, cytokines, tumor necrosis factor and lipopolysaccharides in situations of stress. [14][15][16] An over expression of COX-2 protein and an increased production of prostaglandins have been reported in patients with colon cancer, [17][18][19] and inhibition of the COX-2 enzyme has been a drug target over the past fifteen years. Today, there are several specific COX-2 inhibitors available on the market, but some of these synthetic drugs were recently reported to have severe side effects on the cardiovascular system.…”
Section: )mentioning
confidence: 99%
“…The difference in findings between these studies and ours could be because of cell specificity (none of these cells are immune cells) or different stimuli. The only study that has shown PI3K inhibition increasing COX2 is a study by Weaver et al (61). Using colonic epithelial cell lines, they showed that the inhibitor wortmannin increased COX2 protein, and the inhibitor LY294002 increased COX2 mRNA.…”
Section: Fig 11 Lps-induced Akt Activity Is Correlated Inversely Withmentioning
confidence: 99%